Penggunaan Metode Agile Scrum Pada Perancangan Sistem Informasi Surat Izin Penelitian di BAKESBANGPOL Lombok Tengah - Nico Abrarsyah Atallah; Mardi Mardi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research method examines the application of the Agile Scrum method in designing the research permit information system at Bakesbangpol Central Lombok. The Agile method was chosen because of its ability to accommodate rapid change and increase collaboration between the development team and stakeholders. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews and literature study. The system development process starts from needs analysis, design using Unified Modeling Language (UML), to implementation and testing. The research results show that the Agile Scrum method is effective in increasing the efficiency and quality of the information system being developed. The implementation of this web-based information system is expected to speed up the process of issuing research permits and improve services at Bakesbangpol Central Lombo